2016
DOI: 10.4103/0019-5545.196847
|View full text |Cite
|
Sign up to set email alerts
|

Staff and caregiver attitude to coercion in India

Abstract: Objectives:The objective of this study was to assess attitudes of Indian psychiatrists and caregivers toward coercion.Materials andMethods: The study was conducted at the Department of Psychiatry, Krishna Rajendra Hospital, Mysore, India. Staff Attitude to Coercion Scale (SACS), a 15-item questionnaire, was administered to self-selected psychiatrists across India and caregivers from Mysore to measure attitudes on coercion. Data were analyzed using descriptive statistics and investigating differences in subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 29 publications
0
33
0
3
Order By: Relevance
“…It concluded that the lack of resources is one of the reasons for coercion in India. [17] The drawback of the previous study was that it used SACS which was developed to look at the attitude of coercion among mental health professionals. It was not meant for caregivers, and it was not suitable to assess the ground reality and attitude of Indian caregiver population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It concluded that the lack of resources is one of the reasons for coercion in India. [17] The drawback of the previous study was that it used SACS which was developed to look at the attitude of coercion among mental health professionals. It was not meant for caregivers, and it was not suitable to assess the ground reality and attitude of Indian caregiver population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the majority of caregivers are males and is middle-aged (mean age of 44 years), these findings are in line with the Mysore study findings. [17] Caregivers, who stayed with patients during IP, are mostly family members and from low socioeconomic status. Our study shows that the patients suffering from a severe mental illness such as schizophrenia and other psychotic disorder was 48% and those suffering from mood disorders was 43.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two studies focused on coercion; one study examined prevalence of coercive measures141 and one study explored how the experience of staff might contribute to the use of restrictive practices 210. The attitudes of staff,142 144 211–222 patients145 223–226 and mixed groups143 168 227–230 towards coercion were explored in 25 studies, and 5 studies examined the process of coercive interventions139 140 231 232 and rules of engagement in caring for aggressive patients 233…”
Section: Resultsmentioning
confidence: 99%
“…The practice of restraint and attempts to reduce its use by alternative methods have been attempted in various clinical settings such as (a) acute psychiatry ward,[ 4 7 ] (b) long stay homes for mentally retarded and patients suffering from severe and chronic mental illness, (c) child psychiatry wards,[ 8 ] and (d) elderly care nursing homes. [ 7 ] Restraint in acute psychiatry ward is predominantly used as a means to control aggression and in turn decrease the harm to self and others,[ 9 10 11 ] whereas in child psychiatry wards and long-stay homes, it is used to control problem behaviors. [ 8 ] It is used in elderly nursing homes as a means to decrease the mobility of the patient so as to ease the process of care and to decrease the injuries to self.…”
Section: Types Of Restraintsmentioning
confidence: 99%